2018
DOI: 10.1016/j.cis.2017.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Viscous dynamics of drops and bubbles in Hele-Shaw cells: Drainage, drag friction, coalescence, and bursting

Abstract: In this review article, we discuss recent studies on drops and bubbles in Hele-Shaw cells, focusing on how scaling laws exhibit crossovers from the three-dimensional counterparts and focusing on topics in which viscosity plays an important role. By virtue of progresses in analytical theory and high-speed imaging, dynamics of drops and bubbles have actively been studied with the aid of scaling arguments. However, compared with three-dimensional problems, studies on the corresponding problems in Hele-Shaw cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…Some considered that the regime is realized by elastic feature of entangled polymers and termed the regime "viscoelastic" [24][25][26], while others showed that this regime can be reproduced in a purely viscous liquid via numerical simulation and analytical theory [27][28][29].While there still remains a controversy even for nonconfined three-dimensional (3D) bursting, studies have been very limited for bursting of spatially confined films suspended in air despite their fundamental importance. In fact, a recent study on liquid-drop coalescence [8,30] suggests the importance of the study of confined quasi two-dimentional (2D) bursting in air, demonstrating distinct confinement effects on the dynamics. In addition, such a con-fined dynamics should play fundamentally important roles in many practical applications such as related to foams [31][32][33], given that any films in foam are inherently confined by Plateau borders.…”
mentioning
confidence: 99%
“…Some considered that the regime is realized by elastic feature of entangled polymers and termed the regime "viscoelastic" [24][25][26], while others showed that this regime can be reproduced in a purely viscous liquid via numerical simulation and analytical theory [27][28][29].While there still remains a controversy even for nonconfined three-dimensional (3D) bursting, studies have been very limited for bursting of spatially confined films suspended in air despite their fundamental importance. In fact, a recent study on liquid-drop coalescence [8,30] suggests the importance of the study of confined quasi two-dimentional (2D) bursting in air, demonstrating distinct confinement effects on the dynamics. In addition, such a con-fined dynamics should play fundamentally important roles in many practical applications such as related to foams [31][32][33], given that any films in foam are inherently confined by Plateau borders.…”
mentioning
confidence: 99%
“…In the singly and doubly confined cases, L is significantly larger and smaller than 2r, respectively. The singly confined case corresponds to experiments using Hele-Shaw cells [13,[15][16][17]. In summary, in this paper, we distinguish the following two cases as illustrated in Figs.…”
Section: Methodsmentioning
confidence: 88%
“…[13], and the necessary condition in a more general case in which an air bubble could be replaced with a fluid bubble was established in Refs. [15,16]. The underlining physics is the competition between two extreme cases: one case in which the flow velocity gradient develops only inside a fluid drop and the other in which it develops only inside the thin liquid films.…”
Section: A Rising Velocity In the Doubly Confined Regimementioning
confidence: 99%
See 1 more Smart Citation
“…(1) and (2). The falling velocity U could be determined by the balance between the gravitational energy gain ∆ρgR 2 D 0 U per time and an appropriate viscous dissipation, which should be the most dominant one among the following three [41]: dissipation associated with the Couette flow developed inside thin films between the disk surface and the cell wall ≃ η(U/e) 2 R 2 e and dissipations associated with Poiseuille flows around the disk corresponding to the velocity gradient in the y direction ≃ η(U/D) 2 R 2 D and in the radial direction for the disk ≃ η(U/R) 2 R 2 D. The last dissipation may be smaller than the first two because e, D ≪ R. However, the relative importance of the first and second is delicate; while the volume of dissipation for the first is well described by 2πR 2 D, that for the second can be π(cR) 2 D with a fairly large numerical constant c. In the present case, c seems indeed fairly large and the second dissipation seems the most dominant. This is because the balance of this dissipation and the gravitational energy gain gives U ≃ ∆ρgD 2 /η, which is consistent with Eq.…”
Section: Discussionmentioning
confidence: 99%